Postoperative Magnetic Resonance Imaging following Arthroscopic Primary Anterior Cruciate Ligament Repair - Jelle P. van der List; Douglas N. Mintz; Gregory S. DiFelice (Advances in Orthopedics)
Introduction. Recently, there has been a resurgence of interest in arthroscopic primary anterior cruciate ligament (ACL) repair. To date, no studies have assessed the role of postoperative magnetic resonance imaging (MRI) on the status and maturation of the repaired ligament. The goal of this study was therefore to assess (I) the accuracy of MRI on rerupture of the repaired ligament and (II) the maturation of the repaired ACL. Methods. All postoperative MRIs of patients that underwent arthroscopic primary ACL repair were included. A musculoskeletal radiologist, blinded for MRI indication, surgery-MRI time interval, and clinical stability, retrospectively assessed the ligament continuity and graded ligament maturation as hypointense (similar to intact PCL), isointense (>50% similar to PCL), or hyperintense (<50% similar to PCL). Results. Thirty-seven MRIs were included from 36 patients. Mean age was 30 years (range: 14–57 years), and mean surgery-MRI interval was 1.5 years (range: 0.1–4.9 years). The radiologist recognized 6 out of 8 reruptures and 26 out of 29 intact ligaments (sensitivity 75%, specificity 90%, and accuracy 86%). Ligaments in the first year were more often hyperintense than after one year (60% vs. 11%, p=0.02), most often isointense (60%) between one and two years, and more often hypointense after two years than before two years (56% vs. 10%, p=0.03). Conclusion. Postoperative MRI was found to accurately predict the rerupture of the primarily repaired ACL. Furthermore, it can be expected that the repaired ligament is hyperintense within the first year, while the signal becomes similar to the intact PCL after two years.